Proposed New Positioning and Omnichannel Strategy of Local Fragrance (Case Study: House of Medici) - Carolina Raras Ajeng Daniswara; Asnan Furinto (AIBPM Publisher, 2021)
Local product brands are growing rapidly and many new brands are emerging with quality that is competitive with foreign brands. This indicates that there is intense competition in the local cosmetic product industry. According to a consumer survey by Deloitte in 2018, it still shows that local products dominate the market. House of Medici is a fragrance brand from Indonesia that focuses on perfume products. This research method uses a qualitative approach and a descriptive survey method. Primary data was taken by conducting interviews with the owners and a questionnaire survey. Internal analysis uses STP (Segmenting, Targeting, and Positioning) and 7 P's Marketing Mix. On the other hand, external analysis is carried out with PESTEL and competitor analysis. Furthermore, analyzed using SWOT. Value proposition canvas and omni channel strategy are used for strategy formulation. The results show that current condition of House of Medici with its competitors and needed an Online to Offline strategy that is connected to an omni channel strategy in order to build an integrated distribution platform and marketing channel.